Carbon steel recontamination by Co-60 incorporation into iron (II) oxalate dihydrate formed during chemical decontamination. Issue 1 (2nd January 2021) - Ito, Tsuyoshi; Hosokawa, Hideyuki; Yanagisawa, Shintaro; Ohira, Takashi; Nagase, Makoto
ABSTRACT: Hitachi has developed the chemical decontamination method to remove radioactive oxides on structural materials by alternately using a mixed solution of oxalic acid and hydrazine for a reductive process and potassium permanganate or permanganic acid solution for an oxidative process. In the decontamination of carbon steel (CS) by applying oxalic acid, a film of iron(II) oxalate dihydrate that has low solubility is formed on the CS surface. During the formation of iron(II) oxalate dihydrate, Co-60 in the reductive decontamination solution may be incorporated into the formed film. This phenomenon may cause a decrease in the decontamination efficiency of the CS. A corrosion test of CS in a reductive decontamination solution containing Co-60 as tracer was carried out in order to evaluate this recontamination. It was confirmed that Co-60 was incorporated into the iron(II) oxalate dihydrate film, and the amount of Co-60 increased with increasing formation of this film. About 50% of the Co-60 added to the reductive decontamination solution was incorporated into iron(II) oxalate dihydrate formed on the CS and the Co-60 incorporation ratio was proportional to the iron(II) oxalate dihydrate formation. This result means that the recontamination during chemical decontamination of CS can be predicted.